ColE1-Plasmid Production in Escherichia coli: Mathematical Simulation and Experimental Validation - Freudenau, Inga; Lutter, Petra; Baier, Ruth; Schleef, Martin; Bednarz, Hanna; Lara, Alvaro R.; Niehaus, Karsten (Frontiers in Bioengineering and Biotechnology, 2015)
Plasmids have become very important as pharmaceutical gene vectors in the fields of gene therapy and genetic vaccination in the last years. In this study, we present a dynamic model to simulate the ColE1-like plasmid replication control, once for a DH5α-strain carrying a low copy plasmid (DH5α-pSUP 201-3) and once for a DH5α-strain carrying a high copy plasmid (DH5α-pCMV-lacZ) by using ordinary differential equations (ODE) and the MATLAB software. The model includes the plasmid replication control by two regulatory RNA molecules (RNAI and RNAII) as well as the replication control by uncharged tRNA molecules. To validate the model, experimental data like RNAI- and RNAII concentration, plasmid copy number (PCN), and growth rate for three different time points in the exponential phase were determined. Depending on the sampled time point, the measured RNAI and RNAII concentrations for DH5α-pSUP 201-3 reside between 6 ±0.7 to 34 ±7 RNAI molecules per cell and 0.44 ±0.1 to 3 ±0.9 RNAII molecules per cell. The determined plasmid copy numbers (PCN) averaged between 46 ±26 to 48 ±30 plasmids per cell. The experimentally determined data for DH5α-pCMV-lacZ reside between 345 ±203 to 1086 ±298 RNAI molecules per cell and 22 ±2 to 75 ±10 RNAII molecules per cell with an averaged PCN of 1514 ±1301 to 5806 ±4828 depending on the measured time point. As the model was shown to be consistent with the experimentally determined data, measured at three different time points within the growth of the same strain, we performed predictive simulations concerning the effect of uncharged tRNA molecules on the ColE1-like plasmid replication control. The hypothesis is that these tRNA molecules would have an enhancing effect on the plasmid production. The in silico analysis predicts that uncharged tRNA molecules would indeed increase the pDNA production.